Biodegradation of 2-fluorobenzoate in upflow fixed bed bioreactors operated with different growth support materials - Emanuelsson, Maria A.E. (2010)
Three upflow fixed bed bioreactors treating an aqueous stream containing 2-fluorobenzoate were operated for a period of 7months, during which they were exposed to high organic loading rates and starvation. The reactors contained granular activated carbon (GAC), polyethylene (PE) particles and expanded clay (EC) respectively as growth support for microbial biofilms. The performance of the reactors was compared and the biofilm microbial population was followed by cell counting and denaturing gradient gel electrophoresis (DGGE). The reactor containing GAC always had 100% removal efficiency owing to the adsorption properties of thematerial combined with biodegradation. The GAC reactor also recovered better after starvation periods in the sense that it showed more stable behaviour than the reactors containing EC and PE. The highest biological elimination capacity was observed for the reactor containing EC, which reached 200mg day−1 L−1 during reactor start-up, but during long-termoperation the reactor containing GAC showed the highest biological elimination capacity, 140mg day−1 L−1. DGGE analysis indicated that starvation periods seemed to be responsible for shifts in the microbial population.